Estudos químicos de derivados mesoiônicos do sistema 1,3- Tiazólio-5-tiolato com acetamidas substituídas e suas Potencialidades antifúngicas contra cepas de candida Albicans - Peixoto, Isabelle Nogueira (2016)
This work describes the synthesis, characterization and antifungal potential of twelve mesoionic derivatives from the 1,3-thiazolium-5-thiolate system. The compounds, totally unprecedented, were divided in two classes: one class derived from the mesoionic 2-(4-chlorophenyl)-3-methyl-4-(4-isopropylphenyl)-1,3-thyazolium-5- thiolate with ten substituted acetamides and other class derived from the mesoionic 2- (4-chlorophenyl)-3-methyl-4-(4-methylphenyl)-1,3-thyazolium-5-thiolate also with ten substituted acetamides. This compounds synthesis, which presented satisfactory yields (85 to 95 %), occurred in four stages: first the intermediary N-methyl-Carylglicine was synthesized via Strecker reaction with p-substituted aldehydes, followed by its aroylation to obtain N-methyl-N-aroyl-C-arylglicine, the next step was its cyclodehydration with acetic anhydride, 1,3-dipolar cycloaddition and cyclorevertion induced by CS2 to obtain the mesoionic compounds from the 1,3- thiazolium-5-thyolate as free base. Lastly, the mesoionic compounds were converted into his respective salts by the treatment with ten substituted acetamides. All compounds were characterized by spectroscopic techniques IR, NMR 1H and NMR 13C, and their antifungal potential against five strains of Candida albicans were evaluated. Only four compounds exhibited efficient activity (MI-1-A3, MI-1-A4, MI- 1-A6 and MI-1-A7) with MIC between 256 – 512 μg mL-1. An in silico investigation of the mesoionic compounds, the substituted acetamides and the mesoionic derivatives was also made and the results showed that both mesoionic compounds and his derivatives are good candidates to be a drug while all substituted acetamides should present high toxicity.